RETRACTED: Modern domestic solutions and software for Scandinavian logging in Russia under the new economic conditions - Svoykin F.V.; Zhuk K.D.; Svoykin V.F.; Borozna A.A.; Taraban M.V.; Kretinin V.I.; Uglova L.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001